Knowledge and skills of preschool teachers in implementing a diffrentiated learning aprroach - Kamar, Kancanawati; Abdul Rani, Intan Farahana (Jurnal Pendidikan Bitara UPSI, 2024)
This study was conducted to identify the level of knowledge and skill level of preschool teachers in implementing differentiated learning approaches. This study uses a quantitative approach with a survey design. The selection of the study sample was carried out by simple random sampling and a total of 45 preschool teachers in Beluran District, Sabah were selected as the study sample. This study uses a questionnaire as a research instrument for data collection. This questionnaire contains three parts, namely demographics, knowledge and skills of preschool teachers in implementing differentiated learning approaches. Data were analyzed using descriptive analysis and inferential analysis. Descriptive analysis is used to explain the level of knowledge and skill level of preschool teachers in implementing differentiated learning approaches. Inferential analysis is used to explain the relationship between variables, which is the relationship between the level of knowledge and the skill level of preschool teachers in implementing differentiated learning approaches. The results of the study for the level of knowledge of preschool teachers in implementing a differentiated learning approach is at a high level with a value (mean=4.11, SD=0.804). While the skill level of preschool teachers in implementing differentiated learning approaches is at a high level with values (mean=3.98, SD=0.812). The results of the correlation analysis study show that there is a moderately positive relationship between the level of knowledge and the level of skills of preschool teachers in implementing a value-differentiated learning approach (r=0.524, p